Insights into Mobile Government Adoption Factors: A Comprehensive Analysis of Peduli Lindungi Application in Indonesia - Kurniasih, Denok; Setyoko, Paulus Israwan; Huda, Mohammad Nurul (CommIT (Communication and Information Technology) Journal, 2024)
Information and Communication Technology (ICT) progression has notably impacted the shift from traditional public services to digital alternatives. Among the various digital services, m-government services, provided by smartphone technology, have gained widespread popularity. Unfortunately, the broader adoption of digital technology encounters several challenges, including insufficient user interest and acceptance, as well as concerns regarding security and user privacy. The primary goal of the research is to address the existing gap in the literature by examining the factors that contribute to the effective implementation of m-government services. A mix of key components is employed, incorporating the Information Systems (IS) Success model and Technology Acceptance Model (TAM) as research variables. The research applies a quantitative approach in the form of an online survey. Furthermore, a Partial Least Square- Structure Equational Modeling (PLS-SEM) analytic approach is performed to evaluate 230 data points. The research findings support five hypotheses while rejecting three hypotheses. Significantly, the findings suggest that perceived usefulness and ease of use influence behavioral intention considerably. Additionally, constructions related to service quality significantly impact behavioral intention. Meanwhile, both system quality and information quality do not contribute to affecting behavioral intention. Furthermore, information quality exerts a substantial impact on perceived usefulness, but it does not influence perceived ease of use. Finally, it is observed that system quality significantly affects the perceived ease of use.